Strength of Materials and Structures: An Introduction to the Machines of Solids and Structures - Case (John); Chilver (A H) ("41, Bedford Square,London WCIB 3DQ", 1986)
Strength of Materials ; Structures
Keywords: Strength of Materials ; Structures